2017
DOI: 10.1371/journal.pone.0181649
|View full text |Cite
|
Sign up to set email alerts
|

A novel mitochondrial genome of Arborophila and new insight into Arborophila evolutionary history

Abstract: The lineage of the Bar-backed Partridge (Arborophila brunneopectus) was investigated to determine the phylogenetic relationships within Arborophila as the species is centrally distributed within an area covered by the distributions of 22 South-east Asian hill partridge species. The complete mitochondrial genome (mitogenome) of A. brunneopectus was determined and compared with four other hill partridge species mitogenomes. NADH subunit genes are radical in hill partridge mitogenomes and contain the most potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Among these genes, ND6 and eight tRNA genes (tRNA-Gln, tRNA-Ala, tRNA-Asn, tRNA-Cys, tRNA-Tyr, tRNA-Ser, tRNA-Glu, and tRNA-Pro) located on the light strand (L-strand), whereas other genes located on the heavy strand (H-strand). The insertion of an extra cytosine at position 147 of the ND3 protein-coding sequence and pseudo-control region as in many birds (Song et al 2015;Yan et al 2017;Jiang et al 2019) were not found in P. dedekeni mitogenome.…”
mentioning
confidence: 91%
“…Among these genes, ND6 and eight tRNA genes (tRNA-Gln, tRNA-Ala, tRNA-Asn, tRNA-Cys, tRNA-Tyr, tRNA-Ser, tRNA-Glu, and tRNA-Pro) located on the light strand (L-strand), whereas other genes located on the heavy strand (H-strand). The insertion of an extra cytosine at position 147 of the ND3 protein-coding sequence and pseudo-control region as in many birds (Song et al 2015;Yan et al 2017;Jiang et al 2019) were not found in P. dedekeni mitogenome.…”
mentioning
confidence: 91%
“… 1998 ; Yan et al. 2017 ). However, the base in C. micropterus is replaced by a single ‘A’, which is consistent with the result of some other species of Cuculidae like Cuculus canorus bakeri (Qiu et al.…”
mentioning
confidence: 99%
“…The PCGs have four types of termination codon, including TAA for COX2, ND3, ND4L, ND6, ATP6, ATP8 and Cytb; AGA for ND1 and ND5; AGG for COX1; and an incomplete stop codon T for ND2, ND4, and COX3. It is found that some birds have an extra single 'C' insertion in ND3 (Mindell et al 1998;Yan et al 2017). However, the base in C. micropterus is replaced by a single 'A', which is consistent with the result of some other species of Cuculidae like Cuculus canorus bakeri (Qiu et al 2019), C. poliocephalus (Wang et al 2016) and Eudynamys taitensis (Pratt et al 2009).…”
mentioning
confidence: 99%
“…Some birds have been found to have single insertion mutations in ND3, but the P. rubeculoides has WOC (without extra Cytosine) ND3 (Yan et al. 2017 ). Unlike these mitochondrial genomes of many other bird, which have a pseudo—control region (Song et al.…”
mentioning
confidence: 99%
“…The PCGs have six types of termination codon, including TAA for ATP8, ND3, ND4 and Cytb, TAG for ATP6, AGA for ND1 and ND5, AGG for COX1, 'T--' for COX2, COX3, ND4 and ND6, and 'TA-' for ND2. Some birds have been found to have single insertion mutations in ND3, but the P. rubeculoides has WOC (without extra Cytosine) ND3 (Yan et al 2017). Unlike these mitochondrial genomes of many other bird, which have a pseudo-control region (Song et al 2015), the mitochondrial…”
mentioning
confidence: 99%